Question
upstudy study bank question image url

\( 36 x^{2}+7 x=-2 \) 4 \( 7 x^{2}+24 x=15 \) 5. \( (x+2)(x-3) 50 \)

Ask by Byrd Weston. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: 1. No real solution for \(36x^2+7x=-2\). 2. \(x = -\frac{12+\sqrt{249}}{7}\) and \(x = \frac{-12+\sqrt{249}}{7}\) for \(7x^2+24x=15\). 3. \(x = -7\) and \(x = 8\) for \((x+2)(x-3) = 50\).

Solution

Solve the equation \( 36x^2+7x=-2 \). Solve the equation(The complex numbers system) by following steps: - step0: Solve using the quadratic formula in the complex numbers system: \(36x^{2}+7x=-2\) - step1: Move the expression to the left side: \(36x^{2}+7x+2=0\) - step2: Solve using the quadratic formula: \(x=\frac{-7\pm \sqrt{7^{2}-4\times 36\times 2}}{2\times 36}\) - step3: Simplify the expression: \(x=\frac{-7\pm \sqrt{7^{2}-4\times 36\times 2}}{72}\) - step4: Simplify the expression: \(x=\frac{-7\pm \sqrt{-239}}{72}\) - step5: Simplify the expression: \(x=\frac{-7\pm \sqrt{239}\times i}{72}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{-7+\sqrt{239}\times i}{72}\\&x=\frac{-7-\sqrt{239}\times i}{72}\end{align}\) - step7: Simplify the expression: \(\begin{align}&x=-\frac{7}{72}+\frac{\sqrt{239}}{72}i\\&x=\frac{-7-\sqrt{239}\times i}{72}\end{align}\) - step8: Simplify the expression: \(\begin{align}&x=-\frac{7}{72}+\frac{\sqrt{239}}{72}i\\&x=-\frac{7}{72}-\frac{\sqrt{239}}{72}i\end{align}\) - step9: Rewrite: \(x_{1}=-\frac{7}{72}-\frac{\sqrt{239}}{72}i,x_{2}=-\frac{7}{72}+\frac{\sqrt{239}}{72}i\) - step10: Remove the complex number(s): \(\textrm{No real solution}\) Solve the equation \( 7x^2+24x=15 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(7x^{2}+24x=15\) - step1: Move the expression to the left side: \(7x^{2}+24x-15=0\) - step2: Solve using the quadratic formula: \(x=\frac{-24\pm \sqrt{24^{2}-4\times 7\left(-15\right)}}{2\times 7}\) - step3: Simplify the expression: \(x=\frac{-24\pm \sqrt{24^{2}-4\times 7\left(-15\right)}}{14}\) - step4: Simplify the expression: \(x=\frac{-24\pm \sqrt{996}}{14}\) - step5: Simplify the expression: \(x=\frac{-24\pm 2\sqrt{249}}{14}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{-24+2\sqrt{249}}{14}\\&x=\frac{-24-2\sqrt{249}}{14}\end{align}\) - step7: Simplify the expression: \(\begin{align}&x=\frac{-12+\sqrt{249}}{7}\\&x=\frac{-24-2\sqrt{249}}{14}\end{align}\) - step8: Simplify the expression: \(\begin{align}&x=\frac{-12+\sqrt{249}}{7}\\&x=-\frac{12+\sqrt{249}}{7}\end{align}\) - step9: Rewrite: \(x_{1}=-\frac{12+\sqrt{249}}{7},x_{2}=\frac{-12+\sqrt{249}}{7}\) Solve the equation \( (x+2)(x-3) = 50 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(\left(x+2\right)\left(x-3\right)=50\) - step1: Expand the expression: \(x^{2}-x-6=50\) - step2: Move the expression to the left side: \(x^{2}-x-56=0\) - step3: Factor the expression: \(\left(x-8\right)\left(x+7\right)=0\) - step4: Separate into possible cases: \(\begin{align}&x-8=0\\&x+7=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=8\\&x=-7\end{align}\) - step6: Rewrite: \(x_{1}=-7,x_{2}=8\) The solutions to the given equations are: 1. \(36x^2+7x=-2\) has no real solution. 2. \(7x^2+24x=15\) has two real solutions: \(x_{1}=-\frac{12+\sqrt{249}}{7}\) and \(x_{2}=\frac{-12+\sqrt{249}}{7}\). 3. \((x+2)(x-3) = 50\) has two real solutions: \(x_{1}=-7\) and \(x_{2}=8\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

First, let's rewrite the equations for clarity. The first equation can be simplified to \( 36x^2 + 7x + 2 = 0 \). This showcases a classic quadratic equation format where \( a=36 \), \( b=7 \), and \( c=2 \). Using the quadratic formula - \( x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} \) - will help solve for \( x \) and uncover fashionably hidden roots! Next, for the second equation, rearranging it gives us \( 7x^2 + 24x - 15 = 0 \). Again, this is a quadratic in standard form waiting to be cracked! By applying the quadratic formula, you’ll be able to unveil those elusive solutions. And for the third comment, the expression seems more like a statement or a hint to factorization—if you break it down, it unravels into \( x^2 - x - 6 = 0 \) which is just ripe for factoring into \( (x + 2)(x - 3) = 0 \). Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy